Analysis of the Principles of Good University Governance at the University of Indonesia as a State University with Legal Entity (PTN-BH) in 2014-2019 - Endawansa, Althof; Juwono, Vishnu (Jurnal Borneo Administrator, 2024)
To achieve its vision and mission, the University of Indonesia (UI) has undertaken a series of improvements across various domains, encompassing governance. However, despite these endeavours, the enhancements in UI's governance do not seem to correlate with its performance achievements as documented in the annual reports. This study aims to analyse the application of the principles of good university governance at UI, a state university, from 2014 to 2019. The findings reveal that the execution of good university governance at UI, operating as a State University with a Legal Entity from 2014 to 2019, has not been optimised. The study delineated obstacles to good university governance at UI, encompassing the lack of involvement in decision-making processes beyond the rectorate, particularly in academic management; absence of transparent selection criteria for critical leadership roles such as UI Rectors and Deans; disparities in workload distribution across UI units; and outdated information on the ui.ac.id website. Recommendations stemming from the study advocate for enhancements in regulatory frameworks, refinement of staff performance assessment mechanisms, dissemination of financial regulations, and exploration of avenues to augment non-tuition revenue streams. These proposed measures aim to mitigate the identified challenges and to implement sound university governance principles more effectively at UI